USABILITY EVALUATION OF ERP IXC: a user-centered approach - Lessi Silva, Luís Felipe; Oliani Junior, Santo (Revista Interface Tecnológica, 2023)
The telecommunications industry is undergoing considerable changes in its business environment. The combined efforts of the telecommunications and computing industry have resulted in considerable growth in communications and data service offerings. This trend has put enormous pressure on the business environment of the telecommunications industry, forcing companies to adjust their IT strategies to become more service oriented and to employ new technologies to provide support in terms of integrated services, interoperability, consistent data, customer service network management. The main objective of this study was to suggest a model of strategic and systematic planning and management of resources, infrastructure and processes in Telecom, to promote the financial health of companies expanding in this segment. The research method used in this work was based on books, scientific articles from scientific bases and articles, which is, therefore, bibliographic research. The study allowed us to conclude that the IXC provider and UNM 2000 systems are of paramount relevance to the telecommunications service management process.
Keywords: Management of telecommunication services ERPs; ERPs; Mapping of processes in Telecom